Adolescent users of psychoactive substances: experiences and challenges during psychiatric hospitalization - Pereira, Natália Alonso; da Silva, Meire Luci [UNESP]; Matsukura, Thelma Simões (FapUNIFESP (SciELO), 2023)
Introduction: The scope of care and adherence to treatment of adolescent users of psychoactive substances (PAS) is a challenge for professionals and researchers. Understanding the situational contexts and itineraries taken by adolescents can assist in searching for solutions to this problem. Objective: Identify the experiences and challenges during psychiatric hospitalization from the perception of adolescent users of PSA. Method: This is an exploratory, qualitative study conducted with four adolescents with a history of psychiatric hospitalization, linked to two Psychosocial Care Centers – alcohol and other drugs (CAPSad) in different cities in the interior of the state of São Paulo, Brazil. Data were collected through semi-structured interviews on substance use, life paths and context, therapeutic itinerary, and experiences during hospitalization. The responses were fully transcribed and analyzed using Bardin’s Content Analysis method. Results: The results showed an early start of PAS use, experiences of PAS abuse, vulnerability in the socio-family context, and a history of involuntary hospitalizations. The main challenges experienced and reported by these adolescents during hospitalization were: confinement associated with the long seclusion period, distance from family, lack of safety, and lack of therapeutic approaches. Conclusion: It has become evident that there is a significant challenge in integrating adolescent users of PAS into the Psychosocial Care Network devices within municipalities, as well as into the processes of coordination and accountability of proper care. There is a discrepancy between what is recommended and indicated in public policies and the premises of psychosocial care versus the actual reality of adolescents in psychiatric hospitals.
Adolescentes usuários de substâncias psicoativas: experiências e desafios durante a internação psiquiátrica
Keywords: Adolescent; Drug Users; Involuntary Treatment; Occupational Therapy; Psychiatric; Substance Use Disorders